2024
DOI: 10.1091/mbc.e23-05-0185
|View full text |Cite
|
Sign up to set email alerts
|

BMP signaling to pharyngeal muscle in the C. elegans response to a bacterial pathogen regulates anti-microbial peptide expression and pharyngeal pumping

Emma Jo Ciccarelli,
Moshe Bendelstein,
Katerina K. Yamamoto
et al.

Abstract: Host response to pathogens recruits multiple tissues in part through conserved cell signaling pathways. In C. elegans, the bone morphogenetic protein (BMP) like DBL-1 signaling pathway has a role in the response to infection in addition to other roles in development and post-developmental functions. In the regulation of body size, the DBL-1 pathway acts through cell autonomous signal activation in the epidermis (hypodermis). We have now elucidated the tissues that respond to DBL-1 signaling upon exposure to tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…The BMP-like Ligands DBL-1 and TIG-2 are Independently Required for C. elegans Survival on Bacterial Pathogen C. elegans has five TGF-β like ligands: DBL-1, DAF-7, UNC-129, TIG-2, and TIG-3. It is established that loss of DBL-1, one of two BMP-like ligands in C. elegans, reduces animal survival on bacterial pathogen [35][36]. In a variety of physiological contexts, heterodimers of BMP ligands are functionally required or outperform homodimers [39][40][41][42].…”
Section: Resultsmentioning
confidence: 99%
“…The BMP-like Ligands DBL-1 and TIG-2 are Independently Required for C. elegans Survival on Bacterial Pathogen C. elegans has five TGF-β like ligands: DBL-1, DAF-7, UNC-129, TIG-2, and TIG-3. It is established that loss of DBL-1, one of two BMP-like ligands in C. elegans, reduces animal survival on bacterial pathogen [35][36]. In a variety of physiological contexts, heterodimers of BMP ligands are functionally required or outperform homodimers [39][40][41][42].…”
Section: Resultsmentioning
confidence: 99%
“…Previous work from our lab and others has demonstrated that the BMP homolog DBL-1 functions in the innate immune response of C. elegans to pathogenic bacteria and fungi by inducing the expression of antimicrobial peptide genes in response to pathogen exposure [35][36][37][38]. Here we demonstrate that the DBL-1 ligand is only one of four TGF-β family ligands with a significant role in the immune response to two gram-negative bacterial pathogens.…”
Section: Introductionmentioning
confidence: 50%
“…The BMP-like Ligands DBL-1 and TIG-2 are Independently Required for C. elegans Survival on Bacterial Pathogen C. elegans has five TGF-β like ligands: DBL-1, DAF-7, UNC-129, TIG-2, and TIG-3. It is established that loss of DBL-1, one of two BMP-like ligands in C. elegans, reduces animal survival on bacterial pathogen [35][36]. In a variety of physiological contexts, heterodimers of BMP ligands are functionally required or outperform homodimers [39][40][41][42].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations